2010
DOI: 10.1007/s13197-010-0154-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of juice extraction methods and processing temperature-time on juice quality of Nagpur mandarin (Citrus reticulata Blanco) during storage

Abstract: Influence of juice extraction methods and pasteurization temperature and time on quality of mandarin (Citrus reticulata Blanco) juice was studied. The experiment consisted of 65°C pasteurization temperature with 15, 25 and 35 min holding time; 75°C with 10, 20 and 30 min and 85°C with 5, 10 and 15 min holding times and two types of juice extraction methods. The experiment was laid out in factorial completely randomized Design with three replications. Juice extracted with screw type juice extractor and processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 11 publications
9
16
0
Order By: Relevance
“…Rakha et al, (2017) and Mgaya-Kilima et al, (2014) accredited the increase of reducing sugars in kiwi nectar and mixed hibiscus juice to the conversion of disaccharides into monosaccharides. Pareek et al, (2010) conducted studies on a tangerine juice and agreed with what was said above, adding that in a medium with low pH, acids could turned into reducing sugars.…”
Section: Titrable Aciditysupporting
confidence: 65%
“…Rakha et al, (2017) and Mgaya-Kilima et al, (2014) accredited the increase of reducing sugars in kiwi nectar and mixed hibiscus juice to the conversion of disaccharides into monosaccharides. Pareek et al, (2010) conducted studies on a tangerine juice and agreed with what was said above, adding that in a medium with low pH, acids could turned into reducing sugars.…”
Section: Titrable Aciditysupporting
confidence: 65%
“…These findings are in conformity with Sethi et al, (1980) in long duration Kinnow juice storage at ambient and refrigerated condition. Pareek et al, (2011Pareek et al, ( , 2015 had also reported declining trend of acid loss in mandarin juice during 180 days of storage which was found to be declined at low temperature and high humidity due to reduced conversion of acids in to sugar and salt by invertase enzymes. They had further advocated the minimum loss of acidity during storage when treated with KMS and the loss was found to be reduced as the concentration of KMS increased.…”
Section: Acidity Variation In Fruit Juices During Storagementioning
confidence: 96%
“…One factor that is known to influence extract quality is the extraction method used. Pareek et al [8] in their study also proved that variations in extraction methods carried out could affect the quality of the resulting mandarin juice. Therefore, in this study, an observation was carried out on the fermentation using wheatgrass extract obtained to produce quality fermented beverages.…”
Section: Introductionmentioning
confidence: 86%